Traffic and Ecological Environment of Croatia as Integration Factor in the 21 st Century Europe - Golubić, Jasna; Štrumberger, Nada; Jurum-Kipke, jasna (Promet - Traffic&Transportation, 2012)
Considering the current trends, traffic in 2030 will economicallyand socially burden the society and move away from thesustainability regarding the environment. The paper presentsthe development orientation of the Republic of Croatia in certaintraiiSport branches that will contribute to the efficient environmentalprotection, since protection of the Croatian naturaland civilisation values represents an important strategic orientationof the Republic of Croatia and one of the integration facwrsof the 21'1 century Europe.